Natural products targeting the MAPK signaling pathway: potential options for ulcerative colitis treatment - Li, Canglin; Li, Zuoqiang; Zheng, Ya (Frontiers in Pharmacology, 2026)
As a chronic, recurrent inflammatory bowel disease, ulcerative colitis (UC) poses significant clinical challenges due to its progressive intestinal mucosal damage, recurrent exacerbations of abdominal pain and diarrhea, and increased risk of colorectal cancer conversion with disease duration. Conventional medications such as aminosalicylates and glucocorticoids can control inflammation in the short term, but long-term use often leads to issues like drug resistance, gastrointestinal adverse reactions, and immunosuppression, failing to meet patients’ demand for safe, long-lasting treatment. Natural products, with their wide sources, diverse structures, and rich bioactivity, offer advantages such as multi-targeted effects, low toxicity, and minimal side effects. They demonstrate great potential in treating inflammatory diseases, providing new avenues for UC therapy. Recent studies indicate that various natural products which include flavonoids, alkaloids, terpenoids, and polyphenols can effectively suppress intestinal inflammatory responses, improve intestinal barrier function, and regulate immune balance by targeting the MAPK signaling pathway. This review, using the keywords “ulcerative colitis,” “MAPK,” and “natural products,” retrieved relevant studies from PubMed, Web of Science, and CNKI databases over the past decade. This work identified 42 studies (32 from the past 5 years and 10 from the past 12 years), revealing the mechanisms by which natural products targeting the MAPK signaling pathway function in UC treatment. It provides important theoretical and experimental foundations for developing novel UC treatment strategies based on natural medicines and lays the groundwork for subsequent clinical translation studies of natural products.